Overexpression of Pyruvate Dehydrogenase Kinase-3 Predicts Poor Prognosis in Urothelial Carcinoma - Kuo, Yu-Hsuan; Chan, Ti-Chun; Lai, Hong-Yue; Chen, Tzu-Ju; Wu, Li-Ching; Hsing, Chung-Hsi; Li, Chien-Feng (Frontiers in Oncology, 2021)
Background The mitochondrial pyruvate dehydrogenase complex (PDC) link glycolysis to the tricarboxylic acid cycle by decarboxylating pyruvate to acetyl coenzyme A irreversibly. Cancer cells are characterized by a shift in cellular metabolism from mitochondrial respiration to glycolysis. PDC activity inhibition mediated by phosphorylation via pyruvate dehydrogenase kinase (PDK) has been linked to cancer. However, the clinical significance of PDKs in urothelial cancer prognosis is not clear. We investigated the role and prognostic value of PDK3 expression in patients with upper urinary tract urothelial carcinoma (UTUC) and urinary bladder urothelial carcinoma (UBUC). Patients and Methods: We retrospectively analyzed clinical data and pathological features. Formalin-fixed urothelial carcinoma (UC) tissues were collected and embedded in paraffin. The correlation of PDK3 expression with clinical characteristics, pathological findings and patient outcomes, including metastasis-free survival (MFS) and disease-specific survival (DSS) were analyzed by Pearson’s chi-square test, Kaplan–Meier analysis, and the multivariate Cox proportional hazards model. Results: Data from 295 patients with UBUC and 340 patients with UTUC were evaluated. High PDK3 expression significantly correlated with several pathologic variables such as high T stage, lymph node metastases, high tumor grade, vascular invasion, and high mitotic rate (all P < 0.001). High PDK3 expression was associated with poor disease-specific survival (DSS) (P < 0.0001) and metastatic free survival (MFS) (P < 0.0001) in a Kaplan–Meier analysis. Additionally, multivariate analysis demonstrated increased PDK3 expression is a significant predictive risk factor for DSS [hazard ratio (HR) in UBUC, 2.79, P = 0.009; in UTUC, 2.561, P = 0.03] and MFS (HR in UBUC, 1.907, P = 0.024; in UTUC, 1.793, P = 0.044). The gene co-expression analysis showed abundant PDK3 co-upregulated genes were involved in the processes of DNA replication through the Gene Ontology classification system. Conclusion: High PDK3 expression has been linked to negative pathologic characteristics and poor oncological outcomes, suggesting that it could be used as a predictive biomarker for UC. PDK3 mRNA levels and its co-upregulated genes were strongly associated with DNA replication and repair. These results suggest that PDK3 may play a key role in tumor proliferation and development.